Impact of Internal Audit Practices on Satisfaction of Administrators: A Comparative Study between University of Peradeniya and University of Jaffna, Sri Lanka - Anojan, V.; Nimalathasan, B. (2nd International Symposium on Social Science and Humanities (ISSSH), 2019)
Internal audit plays a major role on overall performance of the organization. Generally internal audit involves with monitoring of internal control, examination of financial and operation information, review of efficiency and effectiveness of operation, review of compliance with laws, regulations, other external requirements, management policies and system. The main purpose of the study is to find out the impact of internal audit practices on satisfaction of administrators in University of Peradeniya and University of Jaffna, Sri Lanka. Primary data was collected from administrators (academic and non-academic administrators) through developed 5 point likert scale questionnaire. This study considered the administrative system review, legal compliance, control on assets usage, control on purchase & procurement and control on payment, research grant & allowance under internal audit practices of Universities. Descriptive analysis revealed that most of the internal audit practices are at moderate level based on administrator’s satisfaction in both universities. Internal audit practices on administrative system review are below moderate level in both universities. Correlation analysis confirmed that there is positive significant relationship between internal audit practices and satisfaction of administrators in above universities. Regression analysis confirmed that there is positive significant impact of internal audit practices related with administrative system review, control on purchase & procurement and legal compliance on internal audit quality in University of Jaffna however there is no significant impact of internal audit practices on administrator’s satisfaction in University of Peradeniya. According to the findings of the study, the top management of both universities and the government should improve internal audit practices in state universities as they have to improve the internal audit practices related to the administrative system review.
Keywords: Administrators; Internal audit practices; Satisfaction